THE EFFECT OF ECONOMIC GROWTH AND HUMAN DEVELOPMENT INDEX ON THE UNEMPLOYMENT RATE IN SOUTH SUMATRA IN 2018-2022 - Puja Nada Sari; Azansyah Azansyah (Journal of Research in Social Science and Humanities, 2025)
This study aims to determine the effect of economic growth and human development index on the unemployment rate in South Sumatra. The data used in this research is secondary data sourced from           with a five-year observation period, namely 2018-2022. The analysis method used in this research is panel data regression. The results showed that economic growth had no effect on unemployment and human development index (HDI) had an effect on unemployment. Meanwhile, together the variables of economic growth and human development index affect the variable unemployment rate in South Sumatra.